ANALYSIS STUDY OF IBNU KHALDUN’S ISLAMIC ECONOMIC THOUGHT - Amri, Ulil (CV. Era Digital Nusantara, 2022)
Activities of economic that are oriented towards the Islamic Economics system are increasingly widespread in various countries, including Indonesia. The theory of Islamic Economics cannot be separated from the thoughts of figures who have contributed to laying the foundations and principles of Islamic economics. Scholars' thinking about Islamic economics in the classical period was very advanced and brilliant, far ahead of modern Western thinkers such as Jean Baptis Say, Ricardo, Adam Smith, and Keynes. Ibn Khaldun is an muslim economy who has a very vital role in the development of Islamic economics to date. This research aims to analyze the thought of Ibn Khaldun to the development of Islamic Economics.